Synthesis of spiro(indoline-2, 3′-hydropyridazine) via an "on-water" [4 + 2] annulation reaction. Issue 5 (7th January 2021) - Zuo, Wei-Fang; Zhou, Jin; Wu, Yu-Ling; Fang, Hua-Ying; Lang, Xing-Jiang; Li, Ya; Zhan, Gu; Han, Bo
Abstract : An on-water [4 + 2] annulation reaction between 2-methyl-3 H -indolium salt and α-bromo N -acyl hydrazone has been developed. The environmentally friendly strategy provides the first facile access to spiro(indoline-2, 3'-hydropyridazine) scaffolds. Abstract : An on-water [4 + 2] annulation reaction between the 2-methyl-3 H -indolium salt and α-bromo N -acyl hydrazone has been developed. The environmentally friendly strategy provides the first facile access to spiro(indoline-2, 3′-hydropyridazine) scaffolds. Compared with the reaction in organic solvents, the use of water as the sole solvent remarkably improves the reaction efficiency as well as chemoselectivity. This green protocol features high yield, broad substrate scope, and mild reaction conditions.